Application of selected stabilizers for the cloud stabilization of kalamansi (Citrus Microcarpa Bunge) juice - Zamora, Myrna Benita Vargas
The most suitable stabilizer and its optimum concentration for cloud stabilization of kalamansi juice was determined in the study. In Phase I, it was found that the stabilizers at their initial concentrations, xanthan gum at 0.15%, guar at 0.10% and propylene glycol alginate at 0.10% were all insufficient in maintaining a stable cloud for one week at 90 to 100°F. Thus in Phase II, the stabilizers were incorporated at increasing levels of 0.20, 0.30, 0.40, 0.50% (W/W) to facilitate selection of the best stabilizer and its appropriate level to create a homogeneous system. Xanthan gum at 0.40 and 0.50% was found to be most effective. For purposes of economy, the lower level of the stabilizer was selected. In Phase III, a storage study of the kalamansi juice with 0.40% was done under accelerated (90-100°F), ambient (82-90°F), and refrigerated (46-54°F) temperatures for one month at weekly intervals. Storage at either ambient or refrigerated temperature is best for kalamansi juice with 0.40% xanthan gum for optimum cloud stabilization.